EVALUATION OF THE COMBINED ANTIBACTERIAL ACTIVITY OF KAEMPFERIA PANDURATA RHIZOME AND SENNA ALATA LEAVES AGAINST METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS - Wikaningtyas, Pratiwi; Sukandar, Elin Yulinah (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objectives: The present study was performed to show the combination in vitro activities of ethanolic extract and ethyl acetate fraction of Kaempferia pandurata and Senna alata against methicillin-resistant Staphylococcus aureus (MRSA). Methods: The antibacterial activities were calculated based on minimum inhibitory concentration (MIC) using microdilution method and minimum bactericidal concentration. The antimicrobial interaction between plant extract with antibiotic was performed using the paper disc and checkerboard method. Results: The similar MIC value was displayed by ethyl acetate fraction of K. pandurata and S. alata (128 µg/mL) while the ethanolic extract of K. pandurata showed lower than S. alata, 512 µg/mL and 256 µg/mL, respectively. The combination between the ethanolic extract of K. pandurata with S. alata showed synergism in all MIC tested and its fraction combination showed synergism in selected MIC value. Conclusions: The observed antimicrobial efficacy and synergistic interactions indicate the beneficial aspects for the MRSA treatment. Keywords: Antimicrobial, Interaction, Kaempferia pandurata, Senna alata, Minimum inhibition concentration, Checkerboard, Synergism.